El tratamiento institucional de los menores que cometen delitos antes de los 14 años - Bernuz Beneitez, María José (Revista Española de Investigación Criminológica, 2006)
The OL 5/2000 Juvenile Criminal Act of 2000 have ordered the regional governments not only to assume the responsibility to respond to juveniles between 14 and 17 who commit crimes, but also to officially respond and work preventively with children of 14 years old that break the law. This law has established the need to work with these children of 14 from the Childhood Protection System; an institution which until those days had worked with classical schemes for children in a vulnerable situation or familiar abandonment, and not on social risk situations. The main objective of this work is to put in the limelight a hardly well-known reality in Spain: crimes committed by children under 14 and measures developed during this time by the institutions that work with them. The results of an empirical investigation made in three Spanish regional governments are shown in this paper: Aragon, Andalusia and Castilla-La Mancha, in which 25% of the children’s files who committed a crime during 2004 have been analyzed and in which legal and social experts who work with children have been interviewed.